‘었’의 의미론과 맥락 - 최성호(Sung-ho Choi) (언어학, 2021)
본 논문은 ‘었’의 기본 의미로 규정한 ‘이미 일어남’이, 통합적으로 인접한 어휘적, 문법적 요소들과 의미론적으로 어떠한 모습으로 상호 작용하는지를 기술하여 그 설명적 타당성을 입증하고자 한다. ‘었’이 보이는 소위 “완료(perfective)”적 해석은 선행 용언의 어휘적 상적 속성([+telos])으로 인해 발생하는 반면, ‘N-부터 (N-까지)’의 부사어 맥락에서는 “퍼펙트”적 해석이 도출되고, 과거를 나타내는 시간 부사어 맥락에서는 “과거”로 해석되는데, 이렇게 맥락적으로 추론되는 해석들은 ‘었’의 기본 의미 ‘이미 일어남’으로 모두 설명 가능하다. 또한 ‘V-었-’이 V-행태가 이미 일어난 상황을 지시한다는 사실이 그러한 상황이 지금 발화 시점에서도 여전히 유효하다고 반드시 함의하는 것이 아니라는 점을 강조하고, 이 점이 ‘었’의 중첩적 사용(즉, ‘었었’)을 동기화한다고 본고는 주장한다. 한편, ‘었’에 후행하는 ‘더’의 맥락(즉, ‘-었던’, ‘-었더니’, ‘-었더라면’)에서 ‘었’이 보이는 의미적 특이성이나 출현 제약들이 본질적으로 의미론적은 문제들임을 설명한다. This paper describes semantic interactions between ‘eoss’ and lexical and grammatical elements that syntagmatically occurs with it, and attempts to prove explanational validity of the proposed basic meaning ‘already taking place’. The perfectivity-interpretation of ‘eoss’ is derived due to the aspectual property [+telos] of the preceding verb; the ‘perfect’-interpretation of ‘V-eoss’ will be possible with the adverb denoting ‘from the past’; further ‘V-eoss’ is interpreted as an event taking place in the past time. These various contextually inferred interpretations are all explicable on the basic meaning of ‘already taking place’. It is pointed out however that ‘V-eoss’ does not necessarily refer to a present-now situation where the event denoted by V is still in effect. It is claimed that the duplicative use of ‘eoss-eoss’ is motivated by this referential vagueness. Finally, this paper argues that the semantic peculiarities and co-occurrence restrictions that ‘eoss’ exhibits in the context of ‘deo’(namely, ‘-eoss-deon’, ‘-eoss-deoni’, ‘-eoss-deoramyeon’) are all essentially semantic issues. KCI Citation Count: 0